(untitled) (Andamios, Revista de Investigación Social, 2014)
In this paper I intend to reread Marx’s famous critique of Human Rights in the trial contended primarily On the Jewish question, written in 1843, from what has been called the thinking of the political. This doomed me, at first, to investigate thoroughly the Marxian text. Then, I discuss the status that would take the “political” in Marx’s thought by the French thinker Miguel Abensour, to finally, try a criticism of Human rRights from reading this new key.